2016
DOI: 10.1002/bio.3105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of UV irradiation on different types of luminescence of SrAl2O4:Eu,Dy phosphors

Abstract: This paper reports the luminescence behavior of Sr Al O :Eu ,Dy phosphors under UV-irradiation. The effect of UV-irradiation on afterglow (AG), thermoluminescence (TL) and mechanoluminescence (ML) of Sr Al O :Eu ,Dy phosphors is investigated. The space group of Sr Al O :Eu ,Dy phosphors is monoclinic P2 . The prepared phosphors exhibit a long AG, intense TL and ML. It is found that the AG, ML intensity and TL increase with increasing duration of irradiation time. The ML intensity decreases with successive impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Photographs of the spray-coated nanocomposite film (RTV-SAO-8) before (Figure 5a) and under (Figure 5b) exposure to UV light for 3 min under ambient conditions, and for a few seconds (Figure 5c) to 60 min (Figure 5d) after turning off the UV lamp are shown in monitored for the photoluminescence characteristics of the nanocomposite film due to such coordinative binding, as the sprayed film demonstrated the same photoluminescence properties as that of powder SAO. [22] Figure 6 shows the UV-vis absorption spectrum of the spray- spectra of SAO arose from the 4f 6 5D 1 $4f 7 transition of Eu(II). [20,57] No…”
Section: Photoluminescence Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Photographs of the spray-coated nanocomposite film (RTV-SAO-8) before (Figure 5a) and under (Figure 5b) exposure to UV light for 3 min under ambient conditions, and for a few seconds (Figure 5c) to 60 min (Figure 5d) after turning off the UV lamp are shown in monitored for the photoluminescence characteristics of the nanocomposite film due to such coordinative binding, as the sprayed film demonstrated the same photoluminescence properties as that of powder SAO. [22] Figure 6 shows the UV-vis absorption spectrum of the spray- spectra of SAO arose from the 4f 6 5D 1 $4f 7 transition of Eu(II). [20,57] No…”
Section: Photoluminescence Measurementsmentioning
confidence: 99%
“…[17][18][19][20] Photoluminescent pigments such as lanthanide-doped strontium aluminium oxide have been used in various applications such as emergency marks and safety clothing. Some long-persistent photoluminescent pigments have been developed to provide different materials of different colours such as Y 2 O 2 S:Mg 2+ ,Ti 4+[ , [21] for red emission, SrAl 2 O 4 :Eu 2+ ,Dy 3+ , [22] for green emission, and CaAl 2 O 4 :Eu 2+ ,Nd 3+ , [23] for blue emission. Strontium aluminium oxide pigments have been the most well known long-persistent photoluminescent materials due to their thermal stability, high chemical stability, nonradioactivity, recyclability, and high quantum efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the ML intensity can be recovered by irradiation from a portable UV lamp ( Figure 4 a ), which replenishes the electrons in traps through continuous exposure. [ 19 , 20 ] Moreover, the irradiation time for complete recovery is determined by factors such as the power of the UV light and the thickness of the sample. Kim and co‐workers found that the ML response depends on the loading rate when the light source for excitation is turned off or when a low‐power light source is used.…”
Section: Principles Of the Mechanoluminescence Of Saoementioning
confidence: 99%
“…[35,36] [37][38][39] They are nonradioactive, reversible, nontoxic, bright, and have high quantum efficiency, are recyclable, and have a long emission time as well as high resistance to light, heat, and chemicals. [40][41][42][43] In this context, lanthanide-doped strontium aluminium oxide phosphor is an extremely beneficial choice to offer fluorescence and photo-switching performance to documents while sustaining their original properties such as appearance, mechanical behaviour, and handle. Therefore, the production of low-cost advanced inks with tuneable photo-switchable characteristics, and that are durable and have enhanced photostability via screen printing with a resin enclosing an inorganic phosphorescent pigment, is an innovative technique.…”
Section: Introductionmentioning
confidence: 99%